2014
DOI: 10.4103/2231-0746.133088
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variation of mandibular canal simulating a recurrence of odontogenic tumor

Abstract: Mandibular nerve has an important role in the field of oral maxillofacial surgery. Furthermore, several anatomical variations can be found and are clinically relevant mainly in procedures involving the posterior mandible. The unknown of these anatomical variations of the inferior alveolar nerve have been implicated with complications in the performance of surgical procedures and anesthesia in dental and maxillofacial practice. The present paper reports a rare anatomical variation of inferior alveolar nerve mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…By knowing the anatomical characteristics of each patient, during various procedures such as tooth extraction, the probability of occurring some iatrogenic lesions such as bleeding, fractures and nervous lesions is very reduce. Although anatomical variations exist, they might increase the complications prevalence (Gioso et al., ; Boudrieau, ; Lommer, ; Guimarães et al, ). Thus, due to the complications and the particularity of each clinical case, it is of great benefit to plan the medical and surgery procedures using information about the localization and size of the mandible anatomical structural elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By knowing the anatomical characteristics of each patient, during various procedures such as tooth extraction, the probability of occurring some iatrogenic lesions such as bleeding, fractures and nervous lesions is very reduce. Although anatomical variations exist, they might increase the complications prevalence (Gioso et al., ; Boudrieau, ; Lommer, ; Guimarães et al, ). Thus, due to the complications and the particularity of each clinical case, it is of great benefit to plan the medical and surgery procedures using information about the localization and size of the mandible anatomical structural elements.…”
Section: Discussionmentioning
confidence: 99%
“…Mandible anatomical variations of the structure elements are a major factor implicated with complications such as overlooked or misdiagnosed of different clinical conditions. The results are particularly important during anaesthesia and surgical procedures in dental and maxillofacial practice, such as exodontias (Guimarães et al., ). Exodontia (tooth extraction) is one of the most commonly used techniques in small animal dental medicine (Girard et al., ; Holmstrom et al., ; Carreira et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Rouas et al (2006) showed how a pseudo-enlarged mandibular canal seen on a panoramic radiograph turned out to have resulted from superimposition over a deep mylohyoid groove when viewed by CBCT. As a recurrent tumor in the vicinity of the mandibular canal has been misdiagnosed, this knowledge will also encourage extra care when dealing with clinical uncertainty (Guimaraes, Pontes, Mata Rezende Ddos, & Pontes, 2014). Added to this problem is the recent finding that tomographic images of pathologies and BMCs often coexist in the molar region (de Castro et al, 2018).…”
Section: Diagnosismentioning
confidence: 99%
“…However, mandibular canal widening is a rare finding. When encountered, several benign and malignant conditions need to be excluded from the list of differential diagnoses before diagnosing it as a normal anatomical variant 34. Clinically, widening of the mandibular canal may be accompanied by sensory disturbances.…”
Section: Introductionmentioning
confidence: 99%